Disrupsi Artificial Intelligence terhadap Pekerja Kreatif Digital: Analisis Opini Publik dan Tren Pasar Kerja Menggunakan Big Data - Haqiqi, Baiq Nurul (Politeknik Statistika STIS, 2025)
The disruption caused by Artificial Intelligence (AI) technology presents new challenges for digital creative workers in Indonesia. On one hand, AI offers efficiency in content production; on the other hand, concerns arise about the displacement of human roles, imitation of artistic styles, and a decline in the originality value of works. This study aims to understand public responses to this phenomenon by leveraging big data through opinion analysis on social media platform X and labor market trend analysis based on job vacancy data from the JobStreet website. Utilizing the IndoBERT language model trained via a few-shot learning approach using the SetFit framework, sentiment analysis reveals a dominance of negative sentiment (65.65%), while emotion detection uncovers that anger (24.34%) and disgust (22.57%) are the most prominent emotional reactions. Public discussions largely highlight issues related to digital art, the use of image generators, animation production, and content automation, which generally reflect concerns about potential shifts in values and roles within the creative industry. Meanwhile, labor market data show that digital creative job vacancies declined in 2025 compared to 2022, with geographic concentration still centered in the Java Island, particularly in Jakarta. The findings of this study are expected to open opportunities for further research to deepen understanding of the impact of AI disruption on digital creative workers and provide an initial overview for related policy formulation.